Genomics of Preaxostyla Flagellates Illuminates the Path Towards the Loss of Mitochondria - Novák, Lukáš V F; Treitli, Sebastian C; Pyrih, Jan; Hałakuc, Paweł; Pipaliya, Shweta V; Vacek, Vojtěch; Brzoň, Ondřej; Soukal, Petr; Eme, Laura; Dacks, Joel B; Karnkowska, Anna; Eliáš, Marek; et al. (PLoS genetics, 2023)
The notion that mitochondria cannot be lost was shattered with the report of an oxymonad Monocercomonoides exilis, the first eukaryote arguably without any mitochondrion. Yet, questions remain about whether this extends beyond the single species and how this transition took place. The Oxymonadida is a group of gut endobionts taxonomically housed in the Preaxostyla which also contains free-living flagellates of the genera Trimastix and Paratrimastix. The latter two taxa harbour conspicuous mitochondrion-related organelles (MROs). Here we report high-quality genome and transcriptome assemblies of two Preaxostyla representatives, the free-living Paratrimastix pyriformis and the oxymonad Blattamonas nauphoetae. We performed thorough comparisons among all available genomic and transcriptomic data of Preaxostyla to further decipher the evolutionary changes towards amitochondriality, endobiosis, and unstacked Golgi. Our results provide insights into the metabolic and endomembrane evolution, but most strikingly the data confirm the complete loss of mitochondria for all three oxymonad species investigated (M. exilis, B. nauphoetae, and Streblomastix strix), suggesting the amitochondriate status is common to a large part if not the whole group of Oxymonadida. This observation moves this unique loss to 100 MYA when oxymonad lineage diversified.
Keywords: Oxymonadida; Genomics; Eukaryota; Phylogeny; fylogeneze; Mitochondria; mitochondrie; genomika